Optimization of engine mounting bracket location - Ilyas, Ishak (2008)
One of the main causes of vibration that produce by a car is engine and transmission. Engine and transmission location determination is an important thing that must be considered for a car. Method of locating engine and transmission will be proposed to determine the right position. This method depends to the size and type of engines. The project objective is to find a location for the engine mounting bracket for a new car. It is important to reduce the vibration from the engine and transmission to the car’s body or chassis. These is also important to fit the engine bay before consider the component of engine clearance with component of body. The stress analysis is done for the location test, different thickness of side member, and different cross section of side member. The FEA software Algor is use for this analysis and Solidwork to modeling the side member. Five different cross section and design are use to analyze the location of the engine mounting bracket. The range location of the mounting bracket is at the middle of the side member. This range depends to the packaging of the engine and the clearance between the components of engine with engine bay. Thickness of the side member also important to decrease the weight of the car and to minimize the stress value when load apply. For conclusion, not all the car has same location of mounting bracket location and many thing must consider before determine this location. The designs of side member influence the location of the mounting bracket.